The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fdgth.2022.939677
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor deficits in Parkinson's disease: Increasing sensitivity using multivariate approaches

Abstract: Parkinson's disease (PD) affects several domains of neurological function, from lower-level motor programs to higher cognitive processing. As certain types of eye movements (saccades) are fast, non-fatiguing, and can be measured objectively and non-invasively, they are a promising candidate for quantifying motor and cognitive dysfunction in PD, as well as other movement disorders. In this pilot study, we evaluate the latency (reaction time), damping (resistance to oscillation), and amplitude of saccadic moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A third possibility is the use of non-somatomotor markers, which may be less affected by symptomatic antiparkinsonian medication. A promising candidate here is the measurement of saccadic eye movements [ 12 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A third possibility is the use of non-somatomotor markers, which may be less affected by symptomatic antiparkinsonian medication. A promising candidate here is the measurement of saccadic eye movements [ 12 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, research has shown that people with AD often display abnormal eye movements on tasks such as pro and antisaccade tasks [ 1 , 32 ]. Cognitive impairment is also well-recognised in Parkinson’s (PD) and similar to AD populations display abnormal eye movements on pro and antisaccade tasks [ 33 , 34 , 35 ]. Due to eye movement variations on well-established paradigms, it cannot be assumed that the previously found SIRE effect will generalise.…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning techniques may also allow identification of more complex patterns of eye movements that will both contribute to diagnosis and to predict disease trajectory. 116 This contribution to diagnosis could be a major step to help triage of patients in pharmaceutical trials.…”
Section: Future Directionsmentioning
confidence: 99%